Governance Innovation for Sustainable Environmental Stewardship in Small Island Regions: Evidence from Ketam Island - Annisa Ilmi Faried; Dian Septiana Sari; Rahmad Sembiring; Saimara Sebayang; Nor Harlinda Binti Harun; Nisa Ulzannah (International Journal of Management, Economic and Accounting, 2025)
This study explores governance innovations that support sustainable environmental stewardship in small island regions, with Ketam Island serving as the central case study. Using a mixed qualitative framework combining institutional analysis, stakeholder mapping, and environmental performance assessment the research identifies how adaptive and collaborative governance mechanisms contribute to ecological resilience. Findings indicate that innovative governance practices, including co-management systems, integrative policy coordination, and community-embedded decision-making, significantly strengthen conservation effectiveness while bolstering local socioeconomic stability. The results further highlight that governance adaptability, transparency, and inclusive participation function as core drivers enabling small island communities to manage environmental risks more effectively. This study concludes that governance innovation provides a scalable model for sustainable island management and offers critical insights for policymakers addressing environmental vulnerabilities in other coastal and archipelagic regions.